2018
DOI: 10.1002/ece3.4607
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of shade management on the taxonomic patterns and functional diversity of termites (Blattodea: Termitidae) in cocoa agroforestry systems

Abstract: Termites have gained importance as major pests in cocoa agroforests. Proper identification of termite species and knowledge on their functional diversity are the first steps in developing environmentally compatible management strategies. We tested the hypothesis that patterns of termite species richness in different cocoa agroforests is related to responses by termite functional groups to changes in shade management. We compared termite assemblages under five cocoa agroforestry systems in Cameroon to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
6
16
0
Order By: Relevance
“…Moist soil and canopy cover can protect termites and microclimate soils (Jamil et al 2017). Canopy cover was positively correlated with diversity and termite abundance (Felicitas et al 2018). As the age of the holder increases, the diversity of termite soils increases.…”
Section: Resultsmentioning
confidence: 99%
“…Moist soil and canopy cover can protect termites and microclimate soils (Jamil et al 2017). Canopy cover was positively correlated with diversity and termite abundance (Felicitas et al 2018). As the age of the holder increases, the diversity of termite soils increases.…”
Section: Resultsmentioning
confidence: 99%
“…These studies suggest natural forests in West African have lower termite species compared with natural forests in Central Africa, and also South America and Asia where termite species richness tends to be higher. For example, in Ecuador Dahlsjö et al (2020) This is consistent with a decline in species numbers due to forest disturbance (Felicitas et al, 2018;Gathorne-Hardy et al, 2001).…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, possibly because the forest community appears somewhat depauperate, termite species richness, abundance, and ies have shown that termite abundance declines with disturbance (Dawes, 2010;Dosso et al, 2013;Felicitas et al, 2018;Vasconcellos et al, 2010), shade trees clearly add some buffering capacity as there was only weak evidence that richness and abundance declined. Deep forest and non-pest termite species were, by in large, maintained under shade trees which provide a relatively conducive environment for termites to survive, especially, the soil-feeding termites (Davies, Eggleton, et al, 2003a;Palin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations